2018
DOI: 10.11591/ijeecs.v12.i3.pp1380-1385
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Framework for Gamified Learning Management System for LINUS Students

Abstract: <p>Gamification is a term that refers to the use of game elements in non-game contexts. Gamification in education is emerging as an effective tool to motivate and engage learners in a variety of tasks. LINUS program is intended to ensure that all students from standard one are able to master the basics of reading, writing and counting at the end of standard three. Gamification will help as a learning tool to assist with the learning process for those who have difficulty in learning, unlike normal student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Now, learning using the gamification approach has begun to be introduced at the Primary, Secondary and Higher Education Institutions. Research shows that various fields have started implementing gamification learning such as STEM [4], Early Child Education [5], Language [6], Linus [7], Mathematics [8][9][10], Mental [11] Medicine [12], Physics [13], Culture [14] and History [15]. This is because, gamification is one of the teaching tool that implement 21 st century learning which is changed from educator-centred learning to student-centred learning [16].…”
Section: Introductionmentioning
confidence: 99%
“…Now, learning using the gamification approach has begun to be introduced at the Primary, Secondary and Higher Education Institutions. Research shows that various fields have started implementing gamification learning such as STEM [4], Early Child Education [5], Language [6], Linus [7], Mathematics [8][9][10], Mental [11] Medicine [12], Physics [13], Culture [14] and History [15]. This is because, gamification is one of the teaching tool that implement 21 st century learning which is changed from educator-centred learning to student-centred learning [16].…”
Section: Introductionmentioning
confidence: 99%
“…Gamification has become an interesting topic for researchers and education practitioners. Gamification is a strategy that integrates game elements into non-game contexts to increase motivation, engagement, and performance [15,[18][19][20][21][22][23][24][25]. In recent years, many studies have been conducted to explore gamification's potential and effectiveness in improving online learning quality.…”
Section: A Gamificationmentioning
confidence: 99%
“…The development of gamified LMS that suits the needs and characteristics of students is essential to help increase student motivation and engagement in online learning. gamified LMS development integrates game elements, such as rewards, challenges, leaderboards, and others [16][17][18][19][20][21][22]. Gamified LMS can be a solution to overcoming the problem of student engagement in online learning that has been emerging.…”
Section: Introductionmentioning
confidence: 99%
“…Gamification can be described as applying the mechanics of games to make learning more fun [10]. Studies have suggested that using gamification approach in students' learning processes can help promote students' interest, motivation, perseverance, and thinking skills [11], [12]. Gamification approach can also improve learning and social interactions as students need to collaborate with other players in completing the structured tasks [8], [13].…”
Section: Literature Reviewmentioning
confidence: 99%